Synthesis, electrochemistry and in situ spectroelectrochemistry of water-soluble phthalocyanines - KOCA, ATIF (SPRINGER, 2009)
The synthesis, characterization and voltammetric and spectroelectrochemical properties of newly synthesized metal-free and metallo phthalocyanines (M = Co, Cu, Zn) containing four dialkylaminophenoxy or trialkylammoniumphenoxy substituents on peripheral positions have been presented in this work. The new compounds have been characterized by using elemental analysis, UV-Vis, FT-IR, H-1 NMR and MS spectroscopic data. Phthalocyanines with trialkylammoniumphenoxy substituents are soluble in aqueous solution over a wide pH range, and these compounds are present as aggregated species in solution as confirmed by the blue shift of Q-bands in their electronic spectra. The electrochemical behavior of the phthalocyanines was investigated by cyclic voltammetry and differential pulse voltammetry on a platinum-working electrode in DCM and DMSO. The voltammetric and spectroelectrochemical measurements of the complexes show that while cobalt phthalocyanine gives both ligand- and metal-based redox processes, metal-free, zinc and copper phthalocyanine complexes give only ligand-based processes in harmony with common phthalocyanine complexes.
Keywords: RECEPTOR FUNCTIONAL PHTHALOCYANINES; METAL-FREE; PHOTODYNAMIC AGENTS; TERTIARY; BEARING; COBALT